2007
DOI: 10.1103/physrevlett.99.037006
|View full text |Cite
|
Sign up to set email alerts
|

Spin Fluctuations and Superconductivity inMo3Sb7

Abstract: Temperature dependences of the magnetic susceptibility, specific heat, and electrical resistivity have been measured for the Mo(3)Sb(7) compound in the 0.6-350 K range. This compound exhibits bulk superconductivity occurring at 2.25 K and follows the Kadowaki-Woods relation, A/gamma(2)=1.0 x 10(-5) microOmega x cm(K x mol/mJ)(2), as a heavy-fermion system does. We show, from experimental evidence and theoretical argument, that Mo(3)Sb(7) can be classified as a coexistent superconductor-spin fluctuation system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 35 publications
8
71
0
Order By: Relevance
“…The occurrence of superconductivity is evidenced by a specific heat jump at 2.2 ±0.05 K. The superconducting phase transition temperature determined from the specific heat measurement is consistent with those obtained from the magnetization and electrical resistivity (not shown here) and with the specific data reported by Candolfi et al [4]. Note, the value of T c observed in the present sample is of about 0.1 K higher than that found in a single crystal of 2.08 K, [1], though specific heat data for single crystal are not yet available.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The occurrence of superconductivity is evidenced by a specific heat jump at 2.2 ±0.05 K. The superconducting phase transition temperature determined from the specific heat measurement is consistent with those obtained from the magnetization and electrical resistivity (not shown here) and with the specific data reported by Candolfi et al [4]. Note, the value of T c observed in the present sample is of about 0.1 K higher than that found in a single crystal of 2.08 K, [1], though specific heat data for single crystal are not yet available.…”
Section: Resultssupporting
confidence: 79%
“…More recently, Candolfi et al [4], have reported magnetic susceptibility, specific heat, and electrical resistivity down to 0.6 K and have interpreted their data within the frameworks of the spin fluctuation theory. Thus, the issue of pairing mechanism becomes debated and the proper superconductivity nature of Mo 3 Sb 7 deserves studies in more details.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] As far as the superconducting pairing mechanism is concerned, there is no agreement whether Mo 3 Sb 7 is a typical s-wave electron-phonon (BCS) superconductor or some more complex state is realized. Most of the published results [2,3,[9][10][11], including first principles calculations for the cubic phase, [11] support the conventional * email: wiendlocha@fis.agh.edu.pl…”
Section: Introductionmentioning
confidence: 87%
“…However, various values of the electronic specific heat jump at the transition point were reported, [3,9,12] ∆C/γT c = 1.04−1.56 much smaller, or close to the weakcoupling BCS value 1.43. Moreover, the specific heat in the superconducting state [9,10] and the magnetic field penetration depth [13,14] behaviors were differently analyzed, in terms of either one-or two-gap BCS models.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation